2021
DOI: 10.47653/farm.v8i1.527
|View full text |Cite
|
Sign up to set email alerts
|

FORMULASI SEDIAAN SABUN PADAT TRANSPARAN MINYAK ATSIRI DAUN JERUK LIMAU (Citrus amblycarpa (Hassk) Ochse) SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus aureus

Abstract: Sabun adalah campuran senyawa natrium atau kalium dengan asam lemak yang berisi sedikit komponen asam miristat atau laurat. Sabun transparan merupakan salah satu inovasi produk menjadikan sabun lebih menarik. Minyak atsiri daun jeruk limau dapat menghambat pertumbuhan bakteri Staphylococcus aureus. Tujuan penelitian ini adalah untuk mengetahui karakteristik fisik sediaan sabun padat transparan minyak atsiri daun jeruk limau dan aktivitas antibakteri terbaik terhadap Staphylococcus aureus. Sampel berupa daun je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The green color in the soap preparation comes from the juice of the leaves of kesum (Polygonum Minus Huds). According to research conducted by (Maulana, 2022), Organoleptic tests, smell tests, shape tests, and color tests were carried out to determine the physical properties of soap preparations. The results of the pH check using universal pH paper showed that the results for soap preparations with concentrations of 15%, 20%, and 25% were 11, and the base control pH was 10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The green color in the soap preparation comes from the juice of the leaves of kesum (Polygonum Minus Huds). According to research conducted by (Maulana, 2022), Organoleptic tests, smell tests, shape tests, and color tests were carried out to determine the physical properties of soap preparations. The results of the pH check using universal pH paper showed that the results for soap preparations with concentrations of 15%, 20%, and 25% were 11, and the base control pH was 10.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture is then poured into a sterile soap mold and allowed to solidify for one to two days (Table 1). (Maulana, 2022) . Test pH.…”
Section: Making Preparation Soap Congestedmentioning
confidence: 99%
See 2 more Smart Citations
“…Sabun merupakan salah satu bentuk sediaan farmasi yang dapat digunakan untuk menjaga kesehatan kulit. Dipasaran, sabun padat transparan lebih sering digunakan oleh masyarakat pada umumnya [3]. Dimana, sabun padat transparaninimerupakan salah satu inovasi sabun yang menjadi kansabun lebih menarik.…”
Section: Pendahuluanunclassified